Business process management as a mechanism for transparency and open government in public entities in Ecuador in 2016-2020 - Cubero Gomezjurado, Juan Pablo (2022)
The Ecuadorian government, as part of the Open Government Partnership, has committed to incorporate mechanisms to enhance the transparency of public information, accountability, and expand the scope of citizen participation in the government. However, current policy and regulations on transparency regarding the opening of public information throughout 2016 and 2020, find limitations to execute mechanisms that fulfill the principles of open government. This article addresses a study of indicators ¾analyzed through qualitative methodology as well as the results introduced by government entities that used quantitative methodology¾ to evaluate the levels of transparency in delivering information. The role of promoting openness of information to stimulate transparency and citizen participation, as constitutive elements of open government, is analyzed. It is concluded that to consolidate open government policies, while providing compliance with current regulations on transparency, it is essential to advance in the introduction of technological infrastructure through a scheme of business management. The final goal would be to arrive to a state of complete openness of public information.